World Health Organization‐defined eosinophilic disorders: 2019 update on diagnosis, risk stratification, and management. Issue 10 (10th September 2019) - Shomali, William; Gotlib, Jason
Abstract: Disease overview: The eosinophilias encompass a broad range of non‐hematologic (secondary or reactive) and hematologic (primary or clonal) disorders with potential for end‐organ damage. Diagnosis: Hypereosinophilia has generally been defined as a peripheral blood eosinophil count greater than 1.5 × 10 9 /L, and may be associated with tissue damage. After exclusion of secondary causes of eosinophilia, diagnostic evaluation of primary eosinophilias relies on a combination of various tests. They include morphologic review of the blood and marrow, standard cytogenetics, fluorescence in situ‐hybridization, flow immunophenotyping, and T‐cell clonality assessment to detect histopathologic or clonal evidence for an acute or chronic hematolymphoid neoplasm. Risk stratification: Disease prognosis relies on identifying the subtype of eosinophilia. After evaluation of secondary causes of eosinophilia, the 2016 World Health Organization endorses a semi‐molecular classification scheme of disease subtypes. This includes the major category "myeloid/lymphoid neoplasms with eosinophilia and rearrangement of PDGFRA, PDGFRB, or FGFR1 or with PCM1‐JAK2 ", and the MPN subtype, "chronic eosinophilic leukemia, not otherwise specified" (CEL, NOS). Lymphocyte‐variant hypereosinophilia is an aberrant T‐cell clone‐driven reactive eosinophila, and idiopathic hypereosinophilic syndrome (HES) is a diagnosis of exclusion. Risk‐adapted therapy: The goal of therapy is to mitigate eosinophil‐mediated organ damage. For patients with milder forms of eosinophilia (eg, <1.5 × 10 9 /L) without symptoms or signs of organ involvement, a watch and wait approach with close‐follow‐up may be undertaken. Identification of rearranged PDGFRA or PDGFRB is critical because of the exquisite responsiveness of these diseases to imatinib. Corticosteroids are first‐line therapy for patients with lymphocyte‐variant hypereosinophilia and HES. Hydroxyurea and interferon‐alfa have demonstrated efficacy as initial treatment and in steroid‐refractory cases of HES. In addition to hydroxyurea, second line cytotoxic chemotherapy agents, and hematopoietic stem cell transplantation have been used for aggressive forms of HES and CEL, with outcomes reported for limited numbers of patients. The use of antibodies against interleukin‐5 (IL‐5) (mepolizumab), the IL‐5 receptor (benralizumab), as well as other targets on eosinophils remains an active area of investigation.